Imposto sobre a renda: lucro arbitrado pressupostos e casos polêmicos - Murphy, Celia Maria de Souza (2010)
The purpose of the present research was to study tax levies over corporate income, and other monetary gains from any source, from the viewpoint of arbitrated earnings in exceptional cases (involving absent or inadequate corporate ledgers), based on the Corporate Income Tax Table and on those prerequisites expressly stated by law. Based on the Constitution, we analyze the concept of income and other monetary gains from any source and conclude that taxes should only be levied over increases in assets over given periods of time. Based on the National Tax Code, we trace the outline of the Basic Structure Governing Income Tax Levies and discuss the three possible methods for establishing the basis of calculation for tax rates. These are: actual earnings, estimated earnings and arbitrated earnings. We then enter into a detailed study of arbitrated earnings, the main object of research, and conclude that such earnings constitute a legal assumption, one that can be challenged by presentation of evidence proving otherwise. We conclude the study with an examination of three controversial situations. These are: (1) legal conditions surrounding self-arbitration of earnings; (2) the problem of deciding on the limits of taxation in the nebulous case of a company possessing partial or inadequate ledgers; and (3) the admissibility of the improperly named conditional arbitration